City Risk Diagnostic for Urban Resilience in Indonesia - Gunawan, Iwan (World Bank, Jakarta, 2016)
In 2012, the World Bank initiated the building urban resilience in East Asia program, aimed at increasing the resilience of cities to disasters and the impact of climate change by using a risk-based approach to making public investment decisions. The objective is to demonstrate a scalable methodology and practical tools for risk assessment that can be used for city-level investment decisions. This activity started with engaging selected cities that have reasonable complexity and are experiencing significant growth. The next step involved conversations about disaster and climate risks confronting the cities and the options that they can consider in building resilience. The result of this experiment is presented in this report. The book begins with two chapters on the disaster and climate vulnerabilities in the context of Indonesian cities, and the basic framework developed by the World Bank building urban resilience in East Asia program. The subsequent two chapters describe the rapid risk diagnostic as the first step in the urban resilience engagement, and the summary of the diagnostic findings in selected Indonesian cities. The final chapter provides a glimpse of how options to invest in resilience can be materialized in practice as part of a city’s development.